Expression of the dspA/E gene of Erwinia amylovora in non-host plant Arabidopsis thaliana - Aksoy, Hasan Murad; Kaya, Yilmaz; Tengku Abdul Hamid, Tengku Haziyamin (Taylor and Francis Ltd., 2017)
In the Erwinia amylovora genome, the hrp gene cluster containing the dspA/E/EB/F operon plays a crucial role in mediating the pathogenicity and the hypersensitive response (HR) in the host plant. The role of the dspA/E gene derived from E. amylovora was investigated by monitoring the expression of the b-glucuronidase (GUS) reporter system in transgenic Arabidopsis thaliana cv. Pri-Gus seedlings. A mutant DdspA/E strain of E. amylovora was generated to contain a deletion of the dspA/E gene for the purpose of this study. Two-week-old seedlings of GUS transgenic Arabidopsis were vacuum-infiltrated with the wild-type and the mutant (DdspA/E) E. amylovora strains. The Arabidopsis seedlings were fixed and stained for GUS activity after 3–5 days following infiltration. The appearance of dense spots with blue staining on the Arabidopsis leaves indicated the typical characteristic of GUS activity. This observation indicated that the wild-type E. amylovora strain had induced a successful and efficient infection on the A. thaliana Pri-Gus leaves. In contrast, there was no visible GUS expression on leaf tissues which were inoculated with the DdspA/E mutant E. amylovora strain. These results indicate that the dspA/E gene is required by the bacterial cells to induce HR in non-host plants.